Implantación de la contabilidad comercial y aplicación de indicadores financieros en Almacen Agropecuario la Chacra del cantón Piñas, período noviembre-diciembre del 2015. - Morales Rodríguez, Xismenia Elizabeth (2017)
This investigative work is fully justified, since, with the accomplishment of the same one will be fulfilling with a requisite for the obtaining of title of Engineer in Accounting and Audit, whose purpose is to consolidate, to consolidate and to increase the acquired knowledge. The exposed work is directed to the accounting and administrative improvement of the agricultural store La Chacra, so that, in this way, it can know the real economic and financial situation of the company, since the correct registration and accounting of all the transactions will be able to optimize the resources Economic and make timely decisions for the achievement of business objectives. In compliance with the objectives proposed in this research was drawn up the plan and manual analysis, information used for the accounting process is systematic and contains uniform registration then detailed inventory of assets was held rights and obligations, information used to proceed to develop the accounting process starting with its initial situation culminating in the preparation of the statement of financial position which reflects the assets, liabilities and equity, income statement showing revenues, costs and expenses to know the change that has taken the heritage for profit or loss for the period, finally the cash flow statement discloses the different movements of cash by operating, investing and financing. Finally we conclude that the proper recording and accounting of all business transactions will enable the owner to make timely decisions to achieve business goals.